1986
DOI: 10.1104/pp.81.4.1103
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Cytokinin Concentrations in Xylem Extrudate following Infection of Eucalyptus marginata Donn ex Sm with Phytophthora cinnamomi Rands

Abstract: ABSTRACIThe concentrations of zeatin-type and isopentenyladenine-type cytokinins were reduced in the xylem extrudate collected from seedlings of Eucalyptus species following infection by Phytophthora cinnamomi Rands. The use of an enzyme-linked immunosorbent assay (ELISA) allowed the detection of these cytokinins over the range of 03 to 7 picomoles for the isopentenyladenine-type and 1 to 1000 picomoles for the zeatin-type. Isopentenyladenine-type cytokinins occurred in concentrations less than 10% of the zeat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
1

Year Published

1990
1990
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(30 citation statements)
references
References 24 publications
(18 reference statements)
1
27
1
Order By: Relevance
“…Earlier reports on the role of cytokinins in the regulation of leaf responses to root environments have often relied on the premise that changes in the levels of cytokinins exported from the roots would cause a reduction in the levels of cytokinins in the leaves (5). In this study, we found that the levels of ZR cytokinins were lower in xylem sap expressed from hypoxic roots than in sap from aerated roots (Fig.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Earlier reports on the role of cytokinins in the regulation of leaf responses to root environments have often relied on the premise that changes in the levels of cytokinins exported from the roots would cause a reduction in the levels of cytokinins in the leaves (5). In this study, we found that the levels of ZR cytokinins were lower in xylem sap expressed from hypoxic roots than in sap from aerated roots (Fig.…”
Section: Discussionsupporting
confidence: 51%
“…The effects of ABA and ZR2 on in vitro leaf growth and the effects of root hypoxia on their endogenous levels in xylem sap and leaves were also measured. (5 discs/dish), containing 10 mL of 10 mm sucrose with 10 mM KCI. Discs from aerated plants grew at similar rates to leaves on the intact plant.…”
mentioning
confidence: 99%
“…These are motile by virtue of their two flagellae and require free water and warm soil conditions for their dispersal (Crandall et al, 1945;Zentmyer, 1980;Shearer and Tippett, 1989 (Shearer and Tippett, 1989). In addition to the root necrosis, there is some evidence that the pathogen may affect host stomatal control by reducing its cytokinin production, leading to crown symptoms resembling those of drought (Cahill et al, 1985(Cahill et al, , 1986. The fungus survives dry periods either as thick-walled chlamydospores embedded in soil or roots, or deep in the soil profile (to 3 m) around infected sinker roots (Shearer and Tippett, 1989).…”
Section: Biology Host Rangementioning
confidence: 99%
“…One relevant factor is that Quercus spp are probably in general more resistant to P cinnamomi than Castanea spp (Crandall et al, 1945 The imposition of drought stress on oaks already exhibiting chronically low levels of root infection might critically reduce their tolerance of the fungus (cf, Griffin et al, 1993). Moreover, drought stress is already known to enhance the development of P cinnamomi within the infected host (Weste and Rupin, 1975;Cahill et al, 1985Cahill et al, , 1986Marçais et al, 1993).…”
Section: Biology Host Rangementioning
confidence: 99%
See 1 more Smart Citation